The Bible and Its Cinematic Adaptations A Consideration of Filmic Exegesis - Burnette-Bletsch, Rhonda 1970- (2014)
This article discusses key theoretical issues pertaining to the Bible’s cinematic reception history. It proposes the term “filmic exegesis” to describe a twofold process of interpretation, which involves both situated filmmakers (at the moment of production) and situated film-viewers (at moments of reception) as active readers of biblical texts. After tracing what has become the dominant scholarly narrative of the Bible’s history in cinema, three methodological points are considered: (1) the need for scholarship to reach beyond the hegemony of Hollywood, (2) the difficulty of establishing clear criteria to define what “counts” as biblical reception in film, and (3) the necessity of moving beyond descriptive cataloguing to critical analysis of the Bible’s filmic afterlives. Finally, this article confronts lingering academic skepticism toward the value of studying the Bible’s popular reception and explains why biblical scholars should bother with filmic exegesis.
Keywords: Biblical Studies; Exegesis; Film; Methodology; Modern